Arterial stiffness in HIV-infected youth and associations with HIV-related variables. Issue 7 (3rd October 2017) - Eckard, Allison Ross; Raggi, Paolo; Ruff, Joshua H.; O'Riordan, Mary Ann; Rosebush, Julia C.; Labbato, Danielle; Daniels, Julie E.; Uribe-Leitz, Monika; Longenecker, Christopher T.; McComsey, Grace A.
ABSTRACT: Children and young adults infected with HIV are at elevated risk for cardiovascular disease (CVD). However, scarce data exist on the utility of non-invasive methods to diagnose subclinical CVD, such as pulse wave velocity (PWV), a non-invasive measure of arterial stiffness. The objectives of this study were to assess the relationship of carotid-femoral PWV with subclinical atherosclerosis measured by carotid intima-media thickness (IMT), compare measurements to healthy controls, and evaluate variables associated with PWV in HIV-infected youth. One hundred and one 8–25 year-old subjects on stable antiretroviral therapy with low-level viremia or an undetectable HIV-1 RNA were enrolled, along with 86 healthy controls similar in age, sex and race. There was no significant difference in PWV between groups (median (Q1, Q3): 5.7 (5.2, 6.3) vs 5.7 (4.9, 6.5) m/s; P = 0.81). Among the HIV-infected subjects, PWV was positively correlated with both internal carotid artery (R = 0.31, P = 0.02) and carotid bulb IMT (R = 0.29, P = 0.01). In multivariable regression, only current alcohol consumption and systolic blood pressure were independently associated with PWV in the HIV-infected group (where current alcohol consumption and higher systolic blood pressure were associated with higher PWV); whereas, age, body mass index, and current marijuana use were associated with PWV in healthy controls. In this study of PWV in HIV-infected youth, measures of arterial stiffness were not different between subjects and controls. However, in HIV-infected youth, there was a significant association between PWV and carotid IMT, as well as between PWV and current alcohol consumption. Thus, PWV may have potential as a useful, non-invasive method to assess CVD risk in HIV-infected youth, but further investigation is needed.